2016
DOI: 10.1007/s10522-016-9659-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of the apolipoprotein E2 allele in age-related disease traits and survival: evidence from the Long Life Family Study

Abstract: The apolipoprotein E (apoE) is a classic example of a gene exhibiting pleiotropism. We examine potential pleiotropic associations of the apoE2 allele in three biodemographic cohorts of long-living individuals, offspring, and spouses from the Long Life Family Study, and intermediate mechanisms, which can link this allele with age-related phenotypes. We focused on age-related macular degeneration, bronchitis, asthma, pneumonia, stroke, creatinine, low-density lipoprotein cholesterol (LDL-C), high-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
2
19
0
1
Order By: Relevance
“…Similar with prior longevity studies (Kulminski et al, 2016;Schachter et al, 1994;Sebastiani et al, 2019), our Case-Control association analyses showed association with increased and decreased frequencies of APOEe2 and APOEe4 haplotypes, respectively, in LLI as compared to controls. As with many prior GWAS studies (Partridge et al, 2018), our analysis revealed APOE as the only locus that was age-associated and replicated in our studies.…”
Section: Discussionsupporting
confidence: 89%
“…Similar with prior longevity studies (Kulminski et al, 2016;Schachter et al, 1994;Sebastiani et al, 2019), our Case-Control association analyses showed association with increased and decreased frequencies of APOEe2 and APOEe4 haplotypes, respectively, in LLI as compared to controls. As with many prior GWAS studies (Partridge et al, 2018), our analysis revealed APOE as the only locus that was age-associated and replicated in our studies.…”
Section: Discussionsupporting
confidence: 89%
“…The current study supports this concept by highlighting strong impact of antagonistic heterogeneity, which is counter-intuitive in medical genetics but natural within the evolutionary framework. The antagonistic heterogeneity is also supported by the analyses of alleles from well-known apolipoprotein B and E genes [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, different, even antagonistic, effects of the same allele on the same phenotype in different population groups are biologically plausible [ 14 , 15 ]. Another challenge in the evolutionary framework is that genetic variants predisposing to a phenotype may not necessarily predispose to another, even causally related, phenotype [ 16 , 17 ] or such genetic variants can predispose to seemingly unrelated phenotypes [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The e 3 allele is the “neutral allele” in many ethnicities, while e 2 is the least common allele that emerged as a longevity variant when Schachter et al noted an increased frequency of e 2 in French centenarians (Schachter et al, ). Since then, several studies have provided evidence that e 2 has a beneficial neuroprotective effect (Kim et al, ), decreases neuroinflammation (Dorey, Chang, Liu, Yang, & Zhang, ), and promotes longevity (Sebastiani, Bae, et al, ; Sebastiani, Gurinovich, et al, ; Sebastiani et al, ) and healthy aging (Kulminski et al, ; Wu & Zhao, ). Therefore, we hypothesize that targets of this allele may lead to the discovery of treatments that help maintain good cognitive function and escape cognitive impairment with aging.…”
Section: Introductionmentioning
confidence: 99%